In-vitro toxicity induced by quartz nanoparticles: Role of ER stress. (1st July 2018) - Sushma; Kumar, Hridyesh; Ahmad, Iqbal; Dutta, Pradip Kumar
Graphical abstract: Highlights: Quartz nanoparticles induce oxidative damage which leads to inflammatory response. ROS mediated mitochondrial depolarization and also accelerated apoptosis. Quartz nanoparticles induce ER stress. Abstract: In recent years with the advancement of nanotoxicology, the scientific communities drastically increased the investigation of the potential toxicity of nanominerals which are present in all atmospheres as well as are used in a variety of applications. In this study, we reported how Quartz Nanoparticles (QNPs) depending on concentration induces different signature ER stress markers in A549 cells. QNPs induced concentration-dependent decrease in cell viability and this concentration dependent toxicity intensifies production of reactive oxygen species leading to oxidative stress and inflammation. Furthermore, the levels of marker proteins of apoptosis (Cytochrome C, Caspase 3, Caspase-12) were found to be significantly up-regulated confirming apoptosis. To check the involvement of ER stress, the activation of ER stress signaling pathway was observed by up-regulated protein levels of ER stress marker proteins including PERK, eIF2α, DDIT3, ATF4 and GRP78 in a concentration-dependent manner. In summary, preliminary assessment of QNPs induced toxicity by monitoring the ER stress signaling pathway gives novel assumptions toward empathizing the effects of QNPs at the cellular level. The adverse effects associated with the exposure to QNPs can be avoided by sensibly using these minerals within the safe dose.